Cross-country evidence on teacher performance pay - Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
The general-equilibrium effects of performance-related teacher pay include long-term incentive and teacher-sorting mechanisms that usually elude experimental studies but are captured in cross-country comparisons. Combining country-level performance-pay measures with rich PISA-2003 international achievement micro data, this paper estimates student-level international education production functions. The use of teacher salary adjustments for outstanding performance is significantly associated with math, science, and reading achievement across countries. Scores in countries with performance-related pay are about one quarter standard deviations higher. Results avoid bias from within-country selection and are robust to continental fixed effects and to controlling for non-performance-based forms of teacher salary adjustments.
Keywords: I20; J33; 330; teacher performance pay; student achievement; international; PISA; Lehrkräfte; Leistungsorientierte Vergütung; Gehalt; Bildungsniveau; Vergleich; Welt